Long-term baited lander experiments at a cold-water coral community on Galway Mound (Belgica Mound Province, NE Atlantic). (November 2017) - Lavaleye, Marc; Duineveld, Gerard; Bergman, Magda; van den Beld, Inge
Abstract: A long-term lander employing a baited camera system was developed to study temporal variation in the presence of scavenging fish and invertebrates at a cold-water coral community on Galway Mound (Belgica Mound Province, NE Atlantic). The camera system was tested during two successful long-term deployments for periods of 6 and 12 months respectively. The baited system, consisting of two separate video cameras with infrared lights and a bait dispenser with 24 bait positions, recorded more than 15, 500 clips of 17 s, regularly spread over both periods. New bait, consisting of sardines in oil, was offered at regular time intervals, and attracted scavengers over the whole period of deployment, and especially the crab Chaceon affinis did still eat from it till the end of the deployments. However, the attractiveness for some scavengers, i.e. amphipods, diminished quite quickly. In addition to invertebrate scavengers, namely C. affinis, two other crab species, amphipods, a shrimp and a starfish, also 7 species of fish were recorded near the bait, of which Lepidion eques was by far the most common. Though there was no concrete evidence for seasonal patterns, the observations showed substantial temporal variation in the abundance of several species, especially the crabs C. affinis and Bathynectes maravigna and the fish Phycis blennoides . It is concluded that long-term deployments of such a baited camera system can produce novel data. For instance such a system could be employed for monitoring impacts of disturbances on the deep-sea floor (e.g. mining), as we infer that mobile scavengers will be among the first organisms to show a visible reaction to any chemically and physically (noise, vibrations) alteration of the environment similar to a mine canary.